The Kepemimpinan Inovasi dan Transformasi dalam Konteks Pendidikan Islam, Studi Kasus Pendidikan Dai di Ma'had Aly Ki Bagus Hadikusumo Sukoharjo - Muh. Fatahillah Suparman; Mudofir; Muhamad Rusdiyanto (At Turots: Jurnal Pendidikan Islam, 2023)
This research aims to explore the potential for innovative behavior change and acceleration efforts in the context of Islamic education at Ma'had Aly Ki Bagus Hadikusumo Sukoharjo through the application of the Innovation Leadership concept (Associating, Questioning, Observing, Experimenting, Networking) and Transformational Leadership. The research methodology employed is qualitative and case study, involving in-depth interviews with institution leaders, staff, and Dai, as well as direct observation of activities and organizational culture. The research findings reveal that the application of the Innovation Leadership concept has driven significant innovative behavior changes among leaders and team members, including increased creativity, experimentation, and collaboration. Furthermore, the Transformational Leadership concept has provided a breakthrough spirit for the organization, enabling acceleration in transformative efforts, allowing the institution to adapt more responsively to changing environmental factors and evolving educational needs. This study provides a profound understanding of how these concepts have been integrated into leadership and organizational culture, and their positive impact on innovative behavior changes and faster transformative efforts in Islamic education at Ma'had Aly Ki Bagus Hadikusumo Sukoharjo.